Association Between Wisdom and Psychotic-Like Experiences in the General Population: A Cross-Sectional Study - Zhipeng Wu (Frontiers in Psychiatry, 2022)
IntroductionWisdom has been empirically researched as a complex psychological characteristic that is associated with many mental health outcomes. However, its association with psychotic-like experiences (PLEs) remains unclear. This is the first work to assess wisdom, explore its association with PLEs, and test its moderating effect on the relation between the frequency of PLEs and their associated distress in the general population.MethodsFrom January 29th to February 5th, 2021, our online self-administered survey recruited 927 participants (ages 14 to 65) from thirteen Chinese provinces. Convenience sampling was employed. We measured wisdom with the 12-item three-dimensional wisdom scale (3D-WS-12) and PLEs with the 15-item positive subscale of the Community Assessment of Psychic Experiences (CAPE-P15).ResultsUsing the cut-off value of 1.47 in the mean frequency score, we divided our participants into high-PLEs group (188, 22.1%) and low-PLEs group (663, 77.9%). Three-dimensional wisdom score was decreased in the high-PLEs group compared to the low-PLEs group (Kruskal-Wallis t = 59.9, p < 0.001). Wisdom was associated with less frequent PLEs (Spearman’s rho = −0.21, p < 0.01) and lower distress related to PLEs (Spearman’s rho = −0.28) in the high-PLEs group (all above p < 0.001), which were replicated in the low-PLEs group. Notably, wisdom significantly attenuated the distress associated with PLEs [coefficient = −0.018, Bootstrap 95% CI (−0.029, −0.008)], but only in the low-PLEs group.ConclusionOur results implicated that wisdom could protect individuals from distressful subclinical psychotic symptoms and wiser individuals have better general mental health.